Evaluation of a Disease State Stewardship Intervention for Urinary Tract Infections at an Academic Medical Center. (October 2020) - Xhemali, Xhilda; Forster, Derek; Clemons, Bryant; Cotner, Sarah; VanHoose, Jeremy; Burgess, Donna; Burgess, David; Myint, Thein; Maskey, Mitu Karki; Wallace, Katie
Abstract : Background: Urinary tract infections (UTIs) are often misdiagnosed and mismanaged. Disease state stewardship initiatives targeting UTIs through the development of institutional guidelines and real-time prospective audit and feedback (PAAF) on provider management may have a significant impact on the overuse of antimicrobials. Objective: Our study evaluated the effectiveness of a UTI focused disease state stewardship intervention by assessing institutional guideline adherence before and after implementation. Methods: This retrospective quasi-experimental study was conducted at a tertiary-care academic medical center. Patients > 18 years of age receiving antimicrobials for a UTI were included. A previously performed retrospective review of UTI management from September-November 2017 was used as the baseline. The UTI management guideline was implemented in July 2018, and service lines were educated. A PAAF initiative began in June 2019, whereby the antimicrobial stewardship team performed daily reviews of patients receiving antimicrobials for UTIs. Data was collected on their management, and providers were contacted in real time with recommendations based on the institutional guideline. Patients reviewed June–October 2019 were included in the postimplementation analysis. Patients were excluded if they were pregnant, underwent a urological procedure with risk of mucosal bleeding, or were an outside hospital transfer already on UTI therapy. The primary outcome of this study was to evaluate guideline adherence before and after the implementation of PAAF for the management of UTIs. Results: In total, 198 patients in the preintervention group and 246 in the PAAF group were included. The emergency department was the primary ordering service of urinalyses (60.1% vs 66.1%; P = .2287) in both periods and altered mental status as the main indication for testing (35.2% vs 31.3%; P = .5465). Treatment of asymptomatic bacteriuria and pyuria decreased significantly between the 2 periods: 74.8% versus 36.2% ( P = .0001). Appropriate ordering of urinalyses (33.8% vs 68.3%; P = .0001) and urine cultures (29.3% vs 61.0%; P = .0001) also improved in the PAAF group. Recommendations made during PAAF included therapy discontinuation (66.7%), antimicrobial therapy change (15.5%), or duration modification (15.5%), and 59.5% of first interventions were accepted. Overall guideline compliance significantly improved from 13.1% in the preintervention period to 26.1% in the PAAF period ( P = .0011). Conclusions: A UTI disease state intervention was associated with significant reductions in the treatment of asymptomatic presentations as well as an improvement in overall guideline adherence. We believe that this approach represents a powerful stewardship strategy for decreasing unnecessary antimicrobial usage. Funding: None Disclosures: None